Mathematics of chance - Anděl, Jiří, 1939-2021 (New York : Wiley, 2001)
Mathematics of Chance utilizes simple, real-world problems-some of which have only recently been solved-to explain fundamental probability theorems, methods, and statistical reasoning. Jiri Andel begins with a basic introduction to probability theory and its important points before moving on to more specific sections on vital aspects of probability, using both classic and modern problems. Each chapter begins with easy, realistic examples before covering the general formulations and mathematical treatments used. The reader will find ample use for a chapter devoted to matrix games and problem sets concerning waiting, probability calculations, expectation calculations, and statistical methods. A special chapter utilizes problems that relate to areas of mathematics outside of statistics and considers certain mathematical concepts from a probabilistic point of view.
Kniha nabízí srozumitelný a zároveň matematicky precizní úvod do teorie pravděpodobnosti a statistického myšlení založený na řešení reálných a často intuitivně uchopitelných problémů. Autor postupuje od základních pojmů pravděpodobnosti k obecnějším větám, metodám a matematickým formulacím, přičemž kombinuje klasické úlohy s moderními problémy, z nichž některé byly vyřešeny teprve nedávno. Jednotlivé kapitoly jsou vystavěny na jednoduchých příkladech, které postupně vedou k abstraktnějšímu a formálnějšímu výkladu. Zvláštní pozornost je věnována maticovým hrám, výpočtům pravděpodobnosti a matematické naděje, problémům čekání a základním statistickým metodám. Samostatná kapitola nahlíží vybrané oblasti matematiky z pravděpodobnostního hlediska a ukazuje mezioborové souvislosti.
Obsahuje bibliografii a rejstřík
Keywords: teorie pravděpodobnosti; pravděpodobnostní metody; statistické metody; monografie; probability theory; probabilistic methods; statistical methods; monographs